1970
DOI: 10.3329/bjo.v16i2.6844
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and degree of hearing loss in chronic suppurative otitis media

Abstract: Objectives: To assess the pattern and degree of hearing loss in CSOM. Methods: A prospective study was carried out from January, 2007 to December, 2008 at the department of Otolaryngology-Head & Neck Surgery, BSMMU, Dhaka This study included 150 cases with 198 ears of CSOM including both tubo-tympanic and attico-antral variety excluding intracranial complications if any. Results: There were 81.31% cases of tubo-tympanic and 18.69% cases of attico-antral patients. Age of the patients was between 5-60 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 9 publications
9
34
1
3
Order By: Relevance
“…In a study by Islam et al, distribution of habitat of the patients were found to be 65.33% from rural area & 34.67% from urban area. 12 Our study is in correlation with this study.…”
Section: Discussionsupporting
confidence: 79%
“…In a study by Islam et al, distribution of habitat of the patients were found to be 65.33% from rural area & 34.67% from urban area. 12 Our study is in correlation with this study.…”
Section: Discussionsupporting
confidence: 79%
“…5 Hearing loss arising from COM is a matter of serious concern because of its long-term effects on communication, language development and educational process. In Bangladesh 16.95% of mild to moderate conductive hearing loss in children and young adults was due to CSOM 4,5 . The degree of hearing loss varies with size and position of tympanic membrane defect, status of ossicular chain and presence of middle ear pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammed Shafiqul Islam et al observed that hearing loss was more in posterior central perforation (51.5 dB) than anterior central perforation (33.64 dB) and the difference between these two sites was statistically significant 9 .…”
Section: Discussionmentioning
confidence: 99%